2007
DOI: 10.1016/j.biopsych.2006.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Greater Cortical Gray Matter Density in Lithium-Treated Patients with Bipolar Disorder

Abstract: Background-The neurobiological underpinnings of bipolar disorder are not well understood. Previous neuroimaging findings have been inconsistent; however, new methods for threedimensional (3-D) computational image analysis may better characterize neuroanatomic changes than standard volumetric measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
175
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 263 publications
(191 citation statements)
references
References 41 publications
13
175
1
2
Order By: Relevance
“…Left ACC gray matter volume is reduced in adult [10] and juvenile [11] bipolar patients. Research employing a statistical parametric mapping approach also revealed reduced gray matter density in the fronto-limbic cortex, particularly in the cingulate [12,13], and in Bearden and colleagues' study [5] greatest differences in gray matter density were found in the bilateral cingulate and paralimbic cortices in lithium-treated bipolar patients (n=20) compared to those not taking lithium (n=8) and healthy controls (n=28). The DLPFC is an understudied region in bipolar disorder, with one study [14] showing significantly smaller gray matter volumes in the left middle and superior, and the right middle and inferior prefrontal regions in 17 bipolar patients hospitalized for a manic episode and receiving various psychotropic medications, and another study demonstrating decreased gray matter volume in the left DLPFC in pediatric bipolar patients [15].…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Left ACC gray matter volume is reduced in adult [10] and juvenile [11] bipolar patients. Research employing a statistical parametric mapping approach also revealed reduced gray matter density in the fronto-limbic cortex, particularly in the cingulate [12,13], and in Bearden and colleagues' study [5] greatest differences in gray matter density were found in the bilateral cingulate and paralimbic cortices in lithium-treated bipolar patients (n=20) compared to those not taking lithium (n=8) and healthy controls (n=28). The DLPFC is an understudied region in bipolar disorder, with one study [14] showing significantly smaller gray matter volumes in the left middle and superior, and the right middle and inferior prefrontal regions in 17 bipolar patients hospitalized for a manic episode and receiving various psychotropic medications, and another study demonstrating decreased gray matter volume in the left DLPFC in pediatric bipolar patients [15].…”
Section: Discussionmentioning
confidence: 88%
“…Another study, although crosssectional, showed that bipolar patients treated with lithium had greater total gray matter volumes than untreated bipolar patients and healthy controls, while there were no significant differences in total white matter volumes across three groups [4]. Also in Bearden and colleagues' study [5], no white matter changes were detected. It is hard to explain why we found total white matter changes in healthy subjects who took lithium for four weeks, as most other studies failed to identify any effects in white matter.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations